Plener „Przestrzeń miasta” – Chełm 1978 - Elżbieta Błotnicka-Mazur (Miejsce)
This article addresses the results of the artistic event ”Space of the City”, organised in Chełm in 1978 by Bożena Kowalska, the then curator of the Galeria 72. She invited 16 artists to create projects for sculptures that were supposed to be delivered later in a material form and located within the space of the city. None of them were eventually realised.